Estimating the endpoint of a uniform distribution under normal measurement errors with known error variance - Hans Schneeweiss (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
The paper studies the problem of estimating the upper end point of a finite interval when the data come from a uniform distribution on this interval and are disturbed by normally distributed measurement errors with known variance. Maximum likelihood and method of moments estimators are introduced and compared to each other.
urn:nbn:de:bvb:19-epub-1717-7
Keywords: 519